Hepatic Proteomic Changes and Sirt1/AMPK Signaling Activation by Oxymatrine Treatment in Rats With Non-alcoholic Steatosis - Xu, Hong; Chen, Gao-Feng; Ma, Yu-Shui; Zhang, Hong-Wei; Zhou, Yang; Liu, Guang-Hui; Chen, Dong-Ya; Ping, Jian; Liu, Yi-Hui; Mou, Xin; Fu, Da (Frontiers in Pharmacology, 2020)
Background: Currently, active ingredients of herbal extracts that can suppress lipid accumulation in the liver have been considered a potential treatment option for nonalcoholic fatty liver disease. Methods: In the present study, steatosis rat model was created by high fat and high sucrose diet feeding and treated with oxymatirne (OMT). Differentially expressed proteins (DEPs) which were significantly changes by OMT treatment in the liver were identified by iTRAQ analysis. L-FABP, Plin2, FASN and SCD1 were chosen for further western blot validation. Results: Our data indicated that OMT significantly reduced the body weight and liver weight of steatosis animals, decreased the serum levels of triglyceride and total cholesterol as well as the hepatic triglyceride and free fatty acid levels, and effectively alleviated fatty degeneration in the liver. DEPs participate mainly in tyrosine metabolism, steroid hormone biosynthesis, starch and sucrose metabolism, retinol metabolism, PPAR signaling pathway. The expressions of L-FABP, Plin2, FASN and SCD1 were decreased significantly by OMT treatment in the liver of steatosis rats. Conclusion: In conclusion, our work provided valuable insights into the molecular mechanism of OMT therapy against steatosis and revealed that L-FABP, Plin2, FASN and SCD1 might be the potential therapeutic targets of OMT therapy for improving nonalcoholic steatosis.